The Dynamic of Blue-Green Algae (Cyanobacteria) in Eutrophic Tropical Waters, The Cirata Reservoir - Fariha Luthfiani; Sunardi Sunardi; Hikmat Kasmara (Indonesian Journal of Limnology, 2020)
The quality of reservoir waters depends on changes in their physical, chemical, and biological components. Changes in these parameters lead to the emerging of many problems in the reservoir, such as eutrophication and changes in the composition of the phytoplankton community in the reservoir ecosystem. This eutrophication impact can trigger an explosion of dangerous phytoplankton population, such as blue-green algae (Cyanobacteria). Research on the relationship between water quality and the community structure of Cyanobacteria has been carried out. This study used secondary data from the water monitoring report of the Cirata Reservoir from 2013-2017. This study aimed to obtain information on the community structure of Cyanobacteria and environmental parameters that affected the abundance of Cyanobacteria in the reservoir. Species abundance, diversity index, and dominance index were analyzed to determine changes in the community structure of Cyanobacteria in each of the years. Cyanobacteria abundances were classified using cluster analysis. Water quality parameters such as temperature, transparency, pH, carbon dioxide, nitrate, nitrite, and zooplankton abundance as independent variables, and levels of Cyanobacteria abundances as the dependent variable was analyzed using discriminant analysis. This study showed that the abundance of Cyanobacteria in the Cirata Reservoir is dominated by the Stanieria (a genus of the Pleurocapsales order) every year and the parameter that significantly affects the level of Cyanobacteria abundance was nitrate (NO3-N).